PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR, KEMAMPUAN PEMECAHAN MASALAH FISIKA DAN MINAT BELAJAR SISWA PADA MATERI FLUIDA STATIS DI SMAN 1 LEBONG SAKTI - Herlinda Herlinda; Eko Wsistoro; Eko Risdianto (UNIB Press, 2017)
This study aims to find the effect of learning model of problem based learning with scientific approach to learning outcomes, to find the effect of learning model of problem based learning with scientific approach to the problem solving ability of physics and to find the influence of learning model of learning based model with scientific approach to learning interest after being taught using Model of problem based learning with a scientific approach. This type of research is Quasi Experiment. The sample was taken using purposive sampling technique obtained by class X IPA 2 as experimental class and class X IPA 3 as control class. Based on the results of data analysis using t test two independent samples indicate there is significant effect of using problem based learning model with scientific approach to learning outcomes tcount (5.65) > ttable (1.68), the ability of solving physics problems with tcount (2.58) > ttable (1.68) and interest in student learning tcount (1.75) > ttable (1.68). So it is concluded that there is a significant influence of the use of problem based learning model with scientific approach to learning outcomes, problem solving skills and interest in experimental class students who taught with the use of problem based learning model with a scientific approach.